Strategi Bertahan Mahasiswa Perantau di Tengah Pandemi Covid-19 di Kota Makassar - Nopri Anti Andau (Universitas Muslim Maros, 2022)
The Covid-19 pandemi has had a number of impacts on students in the City of Makassar. Many students choose to remain in the City of Makassar than to go back to their hometown in the midst of uncertain and insecure conditions from Covid-19. This article discusses the strategies adopted by students in the City of Makassar to survive during the Covid-19 pandemi. This research was conducted in the City of Makassar involving ten students who studied and stayed in this city during the Covid-19 pandemi. They consist of one man and nine women aged between 19 and 21 years, whose come from various tertiary institutions, study programs (prodi), and semesters. I combined in-depth interview and observastion as my data collection methods. The study indicates that many students did not return to their hometown during the Covid-19 pandemi and this was based on three reasons, namely: first, fear that they would be regarded as carriers of the virus when they returned home; second, the fear of being infected with Covid-19 while on the way to their hometown; third, limited facilities and infrastructure that support online lectures in their hometown. However, when they choose to stay in the City of Makassar they face many challenges, and to overcome them they carry out various strategies in order to survive. In general, the survival strategies implemented by these students are divided into three, namely strategies related to preventing Covid-19 by adhering to health protocols, limiting mobility, and keeping busy playing with their cellphones; strategies related to online lectures which consists of solidarity among fellow students and taking advantage of neighbors' help; and strategies for fulfilling daily needsby (utilizing the distribution of groceries by government and regional organization, working part time, living super-efficiently.